Nucleotide Sequence-Based Multitarget Identification - Vinayagamoorthy, T. (American Society for Microbiology, 2003)
MULTIGEN technology (T. Vinayagamoorthy, U.S. patent 6,197,510, March 2001) is a modification of conventional sequencing technology that generates a single electropherogram consisting of short nucleotide sequences from a mixture of known DNA targets. The target sequences may be present on the same or different nucleic acid molecules. For example, when two DNA targets are sequenced, the first and second sequencing primers are annealed to their respective target sequences, and then a polymerase causes chain extension by the addition of new deoxyribose nucleotides. Since the electrophoretic separation depends on the relative molecular weights of the truncated molecules, the molecular weight of the second sequencing primer was specifically designed to be higher than the combined molecular weight of the first sequencing primer plus the molecular weight of the largest truncated molecule generated from the first target sequence. Thus, the series of truncated molecules produced by the second sequencing primer will have higher molecular weights than those produced by the first sequencing primer. Hence, the truncated molecules produced by these two sequencing primers can be effectively separated in a single lane by standard gel electrophoresis in a single electropherogram without any overlapping of the nucleotide sequences. By using sequencing primers with progressively higher molecular weights, multiple short DNA sequences from a variety of targets can be determined simultaneously. We describe here the basic concept of MULTIGEN technology and three applications: detection of sexually transmitted pathogens (Neisseria gonorrhoeae, Chlamydia trachomatis, and Ureaplasma urealyticum), detection of contaminants in meat samples (coliforms, fecal coliforms, and Escherichia coli O157:H7), and detection of single-nucleotide polymorphisms in the human N-acetyltransferase (NAT1) gene (S. Fronhoffs et al., Carcinogenesis 22:1405-1412, 2001).